Spatiotemporal Expression Patterns of Vascular Endothelial Growth Factor and Receptors in Rat Testis and Epididymis throughout Postnatal Development - Özbek, Mehmet; Beyaz, Feyzullah; Hitit, Mustafa; Öztop, Mustafa; Karaca, Harun; Ergün, Emel; Cabir, Ahmet; Ergün, Levent (Research Square Platform LLC, 2024)
Abstract VEGF signaling has a crucial role in regulating the differentiation and proliferation of spermatogonial stem cells, as well as controlling vascular permeability in the epididymis. VEGF primarily exert their effects by binding to VEGFR-1, VEGFR-2, and VEGFR-3. The objective of this work was to assess the expression of VEGF, VEGFR-1, and VEGFR-2 in the rat testis and epididymis during postnatal development using immunohistochemical and Western blotting techniques. The presence of VEGF was exclusively observed in specialized germ cells subsequent to the elongated spermatid stage in the mature phase. VEGF expression was observed in Leydig cells at all phases of postnatal development, but only in mature Sertoli cells throughout the postpubertal and mature periods. Leydig cells demonstrated positive immunostaining for both VEGFR-1 and VEGFR-2, while Sertoli cells showed no positivity for either receptor. VEGFR-1 and VEGFR-2 expression was not observed in germ cells throughout the neonatal and prepubertal phases. VEGFR-1 expression was only present in germ cells at the elongated spermatid stage within the seminiferous tubules during the postpubertal and mature periods. Conversely, VEGFR-2 was detected in both elongated spermatids and spermatogonia. Different levels of VEGF, VEGFR-1, and VEGFR-2 expression were found in different parts of the epididymis. This study reports a differential expression pattern of VEGF, VEGFR-1, and VEGFR-2 in the testis and epididymis during postnatal development. Puberty appears to have an essential impact on overall expression profiles of these proteins. More studies are required to better understand the functions of VEGF and its receptors in male reproductive physiology.